Biology and exploitation of the crucifix crab, Charybdis (Charybdis) feriata (Linnaeus, 1758) (Brachyura: Portunidae) from Karnataka coast, India - Dineshbabu, A. P. (Indian Journal of Fisheries, 2011)
Charybdis feriata supports trawl fishery of Karnataka coast and the entire catch is landed by multiday trawlers operating beyond 30 m depth zone. The highest landing was observed during 2003 (142 t). Fishing season for the species extend generally from September to June but peak fishing season of the species was during December-June. Size range observed in the fishery was 46 to 170 mm in males and 26 to 155 mm in females. Mean size ranged from 66 mm to 80 mm. Test of homogeneity of the sex ratio (χ2 test) for the years, 2007-2009 showed that proportion conform to 1:1 ratio. Studies conducted on reproductive stages of the species show that the species is a continuous breeder with two peak breeding season, one during October–November and another during May-June. Size at maturity (50%) of females was estimated at 70 mm carapace width and age at 50% maturity was about 7 months. Carapace width-weight studies showed that males were heavier than females of similar size. By von Bertalanffy’s growth plot, it was estimated that males and females reach 101mm, 99 mm (CW) respectively at the end of first year and reach 142 mm and 137 mm respectively in two years. Stock assessment studies of the species was conducted using sex pooled data for the period 2007-2009 so as to formulate management suggestions. The Z, M and F values estimated for the species were 6.04, 1.76 and 4.28 respectively. The exploitation ratio (E) was 0.71. MSY was estimated as 131t against the present annual average yield of 124 t. From ‘Thompson and Bell yield prediction analysis’ it is seen that any additional 10% effort from the present level will yield only less than 10% additional catch, indicating that increasing the effort for better catch of the resource will not be economical and it is suggested that restricting the catch to MSY level (131 t) will be the suitable management option for the sustainability of C. feriata fishery from the coast.